Wallander - Season 2 Episode 1-3 - MacDonald, Hettie; Wilson, Andy; Martinovic, Igor; Strebel, Lukas; Branagh, Kenneth; Smart, Sarah; Shimmin, Sadie (2 entertain, 2010)
Kenneth Branagh returns as Inspector Kurt Wallander in the BAFTA award-winning detective drama based on the best-selling books by Henning Mankell – an international publishing phenomenon. In these three new feature length episodes the idyllic tranquillity of Ystad in Southern Sweden is shattered by violence and murder. In "Faceless Killers" an elderly couple are attacked at an isolated farmhouse and the town witnesses an outbreak of racist violence. Wallander is contacted by an old acquaintance who is suspicious about his father’s death in "The Man Who Smiled". An elderly birdwatcher falls to his death in a meticulously planned and brutal murder in "The Fifth Woman". [www.branaghswallander.com]